A reversible phospho-switch mediated by ULK1 regulates the activity of autophagy protease ATG4B - N. Pengo (Nature Portfolio, 2017)
Upon autophagy induction, LC3 is cleaved by the protease ATG4 and conjugated to the autophagosomal membrane; however, its removal is mediated by the same protease. Here the authors show that ULK1-mediated phosphorylation and PP2A-mediated dephosphorylation of ATG4 regulates its cellular activity to control LC3 processing.